Influencia del tiempo de inmersión en soluciones de enzimas proteolícas de pitahaya (hylocereus undatus) sobre la textura de la carne bovina - Zambrano Flores, Freddy Miguel (2019)
The objective of the present investigation was to evaluate the application of enzymatic solutions of the red pitahaya husk to improve the texture of bovine meat in high tenderness cut. The proteolytic enzyme concentrate was extracted, partially purified and dried to make the physicochemical characterization in pH, humidity, protein and enzymatic activity. The enzymes obtained were applied at different concentrations in water 14; 28 and 42 g / L corresponding to factor A, and the time per immersion of the meat for 1 and 2 hours belonging to factor B, resulting in six treatments. For the essay, the Design was completely Randomized plus a witness in three replicas. The experimental unit was the over-rib cutting into uniform pieces of 20 to 25 g. The Meat Texture Profile (TPA) was determined for the meat and an economic estimate was made of all treatments. According to the results, the concentrate with proteolytic enzymes presented 7,78 pH; 11,98% humidity; 7,81% protein and enzymatic activity of 1,386 mol/m3. The variables TPA in the cut of meat managed to establish that the best treatment was the 42 g enzymatic concentration and two hours of immersion, this with an estimated cost of $ 13,37.